A paleontologia e a sala de aula: o contexto local como elo na formação de professores - Hohemberger, Rômulo (2023)
Paleontology is a science that helps human beings understand the origin of life and its evolution through fossils, which make it possible to study and understand the different pre-existing life forms. For this to happen, this subject needs to be addressed in schools and teachers' understanding of paleontological concepts is necessary. In this sense, this thesis aims to develop an educational practice contextualized in the teaching of Paleontology, through a continuing training course based on the Arco de Maguerez methodology for primary school teachers in the city of Mata/RS, in order to provide an understanding of the theme and the local reality, given the abundance of plant fossils present in the community. In this way, research was carried out on the teaching of paleontology, based on theses and dissertations, through a scientometric analysis of the theses and dissertations present in the Brazilian Digital Library of Theses and Dissertations (BDTD) and in the Capes Catalog of Theses and Dissertations. In the second stage of this thesis, a continuing education course was held for teachers from municipal and state schools in the municipality of Mata/RS. The data for this stage of the research was collected at three points: before, during (during the planning and pedagogical intervention) and after the course. Through scientometric analysis, a total of 10 productions were selected, all of which were dissertations. The studies dealt with various contexts of palaeontology, whether in practical applications (pedagogical interventions) or theoretical work, as well as addressing issues such as: guidelines, textbooks, game development, the approach to palaeontology with primary and secondary school students, and teacher training. It was identified that there is a gap in the area, i.e. a field for the development of new proposals for continuing education combined with the teaching of palaeontology. At the time, the teachers' knowledge of palaeontology was fragmented. However, after the course, it became clear that they had a deeper understanding of fossils in general, the fossilization process and the importance of interdisciplinarity in action planning. In the planning and pedagogical intervention phase, it was observed that the research participants approached the concepts as discussed in the training process, using their disciplinary and interdisciplinary knowledge to contextualize the understanding of this science allied to the local reality. Therefore, it was identified that the approach to palaeontology based on the Maguerez's Arc methodology has the potential to address this science, since it explores the relationships between reality and scientific concepts, helping to understand life in a way that is contextualized to the place where the individual is inserted.